1989
DOI: 10.1056/nejm198904133201503
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Lesions and Urinary Albumin Excretion in Type I Diabetes without Overt Proteinuria

Abstract: Since several studies have suggested that a slight increase in urinary albumin excretion (microalbuminuria) is predictive of nephropathy in patients with diabetes mellitus, we studied the relation of albumin excretion to renal structure in patients with insulin-dependent (Type I) diabetes. Renal biopsy specimens were evaluated with light- and electron-microscopical morphometric techniques in 48 patients who had had diabetes for 5 to 40 years and who excreted less than 200 mg of urinary albumin per 24 hours. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
123
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(136 citation statements)
references
References 22 publications
10
123
2
Order By: Relevance
“…Despite being normotensive, our type 1 diabetic patients demonstrated the characteristic lesions of diabetic glomerulopathy, some to quite an extensive degree; other studies have also reported patients with normotension and classical glomerular lesions [30,31].Thus we believe that although this group may not be entirely typical, they are representative.…”
Section: Are the Differences Due To Blood Pressure?contrasting
confidence: 46%
“…Despite being normotensive, our type 1 diabetic patients demonstrated the characteristic lesions of diabetic glomerulopathy, some to quite an extensive degree; other studies have also reported patients with normotension and classical glomerular lesions [30,31].Thus we believe that although this group may not be entirely typical, they are representative.…”
Section: Are the Differences Due To Blood Pressure?contrasting
confidence: 46%
“…These problems are also found in early human diabetic nephropathy. 6,7 In this study, we investigated the hyperfiltration stage, which is separated from the late progression stage. We speculate that this argument might come from the difference of the stage in the development of diabetic nephropathy.…”
Section: Smad1 In Diabetic Nephropathymentioning
confidence: 99%
“…5 Furthermore, extensive studies of the glomerular structure in diabetic patients with or without microalbuminuria failed to find a significant difference in the glomerular structural changes such as mesangial matrix expansion between the two groups in the absence of a raised blood pressure or reduced creatinine (Cre) clearance. 6,7 These reports show that albuminuria might not be a definite marker for mesangial matrix expansion in the early phase of diabetic nephropathy, although albuminuria correlates with and predicts the late development of diabetic nephropathy with decreased GFR and glomerulosclerosis.…”
mentioning
confidence: 99%
“…Aggressive treatment modalities, such as combined therapy with antihyperglycaemic drugs and insulin, appear to decrease the extent of microvascular damage, but are associated with increased incidence of hypoglycaemic events and weight gain [1]. Their risk-to-benefit ratio is high also because less than one third of diabetic patients develop nephropathy [2].Attempts have been made to find a marker that can predict micro-angiopathy in diabetes, and identify a group of patients for whom aggressive treatment is indicated despite its possible adverse effects. Urinary excretion of very small amounts of albumin (microalbuminuria) and elevation of arterial pressure [3] have been proposed for this purpose, but both appear when renal damage is already impending [4].…”
mentioning
confidence: 99%
“…Aggressive treatment modalities, such as combined therapy with antihyperglycaemic drugs and insulin, appear to decrease the extent of microvascular damage, but are associated with increased incidence of hypoglycaemic events and weight gain [1]. Their risk-to-benefit ratio is high also because less than one third of diabetic patients develop nephropathy [2].…”
mentioning
confidence: 99%